Carbon and oxygen geochemistry of the mantle peridotites of the Wadi Tayin Massif, Samail Ophiolite, ICDP Expedition 5057 Oman Drilling Project - Lotta Ternieten; Gretchen L Früh-Green; Stefano M Bernasconi (PANGAEA, 2021)
A large part of the hydrated oceanic lithosphere consists of serpentinites exposed in ophiolites. Serpentinites constitute reactive chemical and thermal systems and potentially represent an effective sink for CO2. Understanding carbonation mechanisms within ophiolites is almost exclusively based on studies of outcrops, which can limit the interpretation of fossil hydrothermal systems. We present stable and radiogenic carbon data that provide insights into the isotopic trends and fluid evolution of peridotite carbonation in ICDP Oman Drilling Project drill holes BA1B (400 m deep) and BA3A (300 m deep). Geochemical investigations of the carbonates in serpentinites indicate formation in the last 50 kyr, implying a distinctly different phase of alteration than the initial oceanic hydration and serpentinization of the Samail Ophiolite. The oldest carbonates (31 to > 50 kyr) are localized calcite, dolomite, and aragonite veins, formed between 26 to 43 °C and related to focused fluid flow. Subsequent pervasive small amounts of dispersed carbonate precipitated in the last 1000 yr. Macroscopic brecciation and veining of the peridotite indicate that carbonation is influenced by tectonic features allowing infiltration of fluids over extended periods and at different structural levels such as along fracture planes and micro-fractures and grain boundaries, causing large-scale hydration of the ophiolite. The formation of dispersed carbonate is related to percolating fluids with 18O lower than modern ground- and meteoric water. Our study shows that radiocarbon investigations are an essential tool to interpret the carbonation history and that stable oxygen and carbon isotopes alone can result in ambiguous interpretations.